Folding and processing of the capsid protein precursor P1 is kinetically retarded in neutralization site 3B mutants of poliovirus. - Reynolds, C (1992)
Poliovirus mutants in neutralizing antigenic site 3B were constructed by replacing the glutamic acid residue at amino acid 74 of capsid protein VP2 (VP2074E), using site-specific mutagenesis methods. All viable mutants display small-plaque phenotypes. Characterization of these mutants indicates that capsid assembly is perturbed. Although the defect in capsid assembly reduces the yield of mutant virus particles per cell, the resultant assembled particle is wild-type-like in structure and infectivity. Analyses of capsid assembly intermediates show a transient accumulation of the unprocessed capsid protein precursor, P1, indicating that cleavage of the mutant P1 by the 3CD protease is retarded. The mutant VP0-VP3-VP1 complex generated upon P1 cleavage appears assembly competent, forming pentamer and empty capsid assembly intermediates and infectious virion particles. Although the structure of the infectious mutant virus is virtually identical with that of the wild-type virus, the thermal stability of the mutant virus is dramatically increased over that of the wild-type virus. Thus, mutations at this residue are pleiotropic, altering the kinetics of capsid assembly and generating a virus that is more thermostable and more resistant to neutralization by the site 3B monoclonal antibodies.